2011
DOI: 10.4161/cbt.11.5.14410
|View full text |Cite
|
Sign up to set email alerts
|

A polymeric nanoparticle formulation of curcumin inhibits growth, clonogenicity and stem-like fraction in malignant brain tumors

Abstract: Curcumin is a polyphenolic compound derived from the Indian spice turmeric. We used nanoparticle-encapsulated curcumin to treat medulloblastoma and glioblastoma cells. This formulation caused a dose-dependent decrease in growth of multiple brain tumor cell cultures, including the embryonal tumor derived lines DAOY and D283Med, and the glioblastoma neurosphere lines HSR-GBM1 and JHH-GBM14. The reductions in viable cell mass observed were associated with a combination of G(2)/M arrest and apoptotic induction. Cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
126
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 207 publications
(129 citation statements)
references
References 49 publications
(64 reference statements)
2
126
0
1
Order By: Relevance
“…In vivo studies of PLGA and polyNI-PAM nanogel curcumin formulations have shown improved bioavailability, and therefore are more effective systems for delivering curcumin into tumors. 12,14,16,72,73 These data clearly support the overall conclusion of this study. Our future research efforts will include evaluation of the in vivo pharmacokinetics of these curcumin nanoformulations to clarify the underlying mechanisms for potential cancer therapeutics.…”
supporting
confidence: 81%
“…In vivo studies of PLGA and polyNI-PAM nanogel curcumin formulations have shown improved bioavailability, and therefore are more effective systems for delivering curcumin into tumors. 12,14,16,72,73 These data clearly support the overall conclusion of this study. Our future research efforts will include evaluation of the in vivo pharmacokinetics of these curcumin nanoformulations to clarify the underlying mechanisms for potential cancer therapeutics.…”
supporting
confidence: 81%
“…In addition to these features, improved cellular uptake and/ or apoptosis induction by CUR nanoformulations result in enhanced anticancer activity in melanoma (Sun et al, 2014b), prostate (Yallapu et al, 2012), cervical Nair et al, 2012;Punfa et al, 2012;Pillai et al, 2014), ovarian (Yallapu et al, 2010a), breast (Yallapu et al, 2010a;Verderio et al, 2013;Mirakabad et al, 2016), colon (Prajakta et al, 2009;, pancreatic (Kim et al, 2011), lung (Teong et al, 2015) medulloblastoma (Lim et al, 2011), glioblastoma (Lim et al, 2011), and oral carcinoma (Popat et al, 2014) cancer cell lines with superior pharmacokinetics . Furthermore, PLGA-PEG nanoparticles are able to enhance the anticancer efficiency of CUR in prostate (Yallapu et al, 2014) and colon (Kim et al, 2011) cancer cell both in vitro and in vivo.…”
Section: Polymeric Nanoparticlesmentioning
confidence: 99%
“…NanoCurcℱ, a recently developed polymeric NP encapsulating curcumin, significantly reduced clonogenic growth and CD133-positive stem-like population in malignant brain tumors. 22 In addition, NPs conjugated with PEGylated poly(lactic-co-glycolic acid) receive extensive attention and are used widely because of their safety in the clinical trials. 77 Interestingly, salinomycin-loaded NPs conjugated with CD133 aptamers selectively inhibit CD133-positive osteosarcoma both in vitro and in vivo.…”
Section: Cd133mentioning
confidence: 99%